2006
DOI: 10.1152/ajprenal.00362.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tempol reduces oxidative stress and restores renal dopamine D1-like receptor- G protein coupling and function in hyperglycemic rats

Abstract: Dopamine via activation of renal D1-like receptors inhibits the activities of Na-K-ATPase and Na/H exchanger and subsequently increases sodium excretion. Decreased renal dopamine production and sodium excretion are associated with hyperglycemic conditions. We have earlier reported D1-like receptor-G protein uncoupling and reduced response to D1-like receptor activation in streptozotocin (STZ)-treated hyperglycemic rats (Marwaha A, Banday AA, and Lokhandwala MF. Am J Physiol Renal Physiol 286: F451-F457, 2004).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 45 publications
6
57
0
Order By: Relevance
“…In addition, Rankin et al (31) have shown that GRKs can phosphorylate D1R in absence of agonist activation, resulting in constitutive desensitization. Our own studies involving animal models associated with oxidative stress such as obese Zucker rats, streptozotocin-treated rats, and Fisher 344 old rats as well as renal proximal tubular cultures exposed to insulin or H 2 O 2 showed that D1R were constitutively phosphorylated and uncoupled from G proteins (3,4,7,27). In addition, we found that treatment of these animals with antioxidants, while reducing oxidative stress, normalized GRK2 sequestration and receptor phosphorylation and restored D1R signaling (7,12,27).…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…In addition, Rankin et al (31) have shown that GRKs can phosphorylate D1R in absence of agonist activation, resulting in constitutive desensitization. Our own studies involving animal models associated with oxidative stress such as obese Zucker rats, streptozotocin-treated rats, and Fisher 344 old rats as well as renal proximal tubular cultures exposed to insulin or H 2 O 2 showed that D1R were constitutively phosphorylated and uncoupled from G proteins (3,4,7,27). In addition, we found that treatment of these animals with antioxidants, while reducing oxidative stress, normalized GRK2 sequestration and receptor phosphorylation and restored D1R signaling (7,12,27).…”
mentioning
confidence: 62%
“…In addition, we found that treatment of these animals with antioxidants, while reducing oxidative stress, normalized GRK2 sequestration and receptor phosphorylation and restored D1R signaling (7,12,27). Although these reports provide substantial evidence related to the role of GRKs in D1R hyperphosphorylation and subsequent desensitization, most of these studies were focused on D1R coupling to G s ␣ and AC activation (6,7,12,27). Numerous studies have demonstrated that renal D1R also mediates its functional effects through activation of the G q/11 ␣ protein and its downstream effector, phospholipase C (PLC) (13,14,40,48).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…A reactive oxygen species-associated defect in renal dopamine type 1 receptor function has been observed not only in experimental models of hypertension (Banday et al, 2008;Hussain et al, 1999;Hussain & Lokhandwala, 1997a;Hussain & Lokhandwala, 1997b) but also in diabetes (Banday et al, 2005;Marwaha & Lokhandwala, 2006) and ageing (Fardoun et al, 2006;Hussain et al, 1999;Vieira-Coelho et al, 1999). Failure of dopamine to modulate sodium reabsorption results in diminished natriuresis and blood pressure elevation.…”
Section: Loss Of Redox Balance: Functional Consequences In Renal Physmentioning
confidence: 99%